2017
DOI: 10.9753/icce.v35.structures.14
|View full text |Cite
|
Sign up to set email alerts
|

Design and Construction of the Western Breakwater for the Outer Port at Punta Langosteira (A Coruã‘a, Spain)

Abstract: This paper describes the design process, hydraulic stability tests and construction of the Cubipod ® armored Western breakwater at Punta Langosteira (Outer Port of A Coruña, Spain), located on the Atlantic coast of Spain. The environmental, geotechnical, economic and logistic conditions favored randomly-placed Cubipods for single-layer armoring of the trunk. 3D hydraulic stability tests were carried out to validate the final design of the Western Breakwater; two models were tested with single-and double-layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…As can be seen in Figure 5, Punta Langosteira is a rubble mound breakwater with concrete blocks in the armor layer around 150 tons [10], with the top of the non-overtopping crown wall at +25.00 m. Torres is a rubble mound breakwater with concrete pieces in the armor layer around 90 tons, with the top of the non-overtopping crown wall at +17.50 m. Norte is a vertical breakwater with 32 × 52 × 32 m caissons, with the top of the crown wall at the same height as Torres breakwater. Punta Lucero is a rubble mound breakwater with concrete blocks in the armor layer around 150 tons, with the top of the non-overtopping crown wall at +21.00 m [9]10. The rest of characteristics of the four breakwaters can be seen in Table 1.…”
Section: Design Basismentioning
confidence: 99%
See 3 more Smart Citations
“…As can be seen in Figure 5, Punta Langosteira is a rubble mound breakwater with concrete blocks in the armor layer around 150 tons [10], with the top of the non-overtopping crown wall at +25.00 m. Torres is a rubble mound breakwater with concrete pieces in the armor layer around 90 tons, with the top of the non-overtopping crown wall at +17.50 m. Norte is a vertical breakwater with 32 × 52 × 32 m caissons, with the top of the crown wall at the same height as Torres breakwater. Punta Lucero is a rubble mound breakwater with concrete blocks in the armor layer around 150 tons, with the top of the non-overtopping crown wall at +21.00 m [9]10. The rest of characteristics of the four breakwaters can be seen in Table 1.…”
Section: Design Basismentioning
confidence: 99%
“…Sci. 2019, 9,5225 14 of 31 maritime climate in average regime were selected [24,25]. In Figures 10-12, different graphic results of the characterization of the maritime climate in the three study points are shown.…”
Section: Hydraulic and Energetic Behaviormentioning
confidence: 99%
See 2 more Smart Citations